APPLICATION OF THE TOOLS OF PRODUCTION ENGINEERING FOR THE REDUCTION OF DEAD TIME IN AN ASSEMBLY LINE - Mello, Mario Fernando (2017)
Abstract: The constant changes in the agricultural equipment market have brought many challenges to the productive sectors inside the organizations. Once the market is increasingly competitive, the industries lack of efficient working methods and companies seek intensely to adapt themselves to a methodology to assist in the standardization of production processes. The main objective of this work is the application of some tools of Production Engineering to improve the operating times in an assembly sector of a metal mechanical industry. The focus is to establish and to define the guidelines of the used methodology, the so-called ‘Just in time’, to seek the reduction of dead time in the process of the assembly line according to the reality of the companies. Change processes are very conditioned to the environment, the culture of who receives them and leads them. Thus, this project also aims to aid in the maturation of the staff in this cultural aspect, seeking the development of operators in a new operating process.